Biological Activity and Molecular Structures of Bis(benzimidazole) and Trithiocyanurate Complexes - Kopel, Pavel; Wawrzak, Dorota; Langer, Vratislav; Cihalova, Kristyna; Chudobova, Dagmar; Vesely, Radek; Adam, Vojtech; Kizek, Rene (Molecules (Basel, Switzerland), 2015)
1-(1H-Benzimidazol-2-yl)-N-(1H-benzimidazol-2-ylmethyl)methanamine (abb) and 2-(1H-benzimidazol-2-ylmethylsulfanylmethyl)-1H-benzimidazole (tbb) have been prepared and characterized by elemental analysis. These bis(benzimidazoles) have been further used in combination with trithiocyanuric acid for the preparation of complexes. The crystal and molecular structures of two of them have been solved. Each nickel atom in the structure of trinuclear complex [Ni3(abb)3(H2O)3(μ-ttc)](ClO4)3·3H2O·EtOH (1), where ttcH3 = trithiocyanuric acid, is coordinated with three N atoms of abb, the N,S donor set of ttc anion and an oxygen of a water molecule. The crystal of [(tbbH2)(ttcH2)2(ttcH3)(H2O)] (2) is composed of a protonated bis(benzimidazole), two ttcH2 anions, ttcH3 and water. The structure is stabilized by a network of hydrogen bonds. These compounds were primarily synthesized for their potential antimicrobial activity and hence their possible use in the treatment of infections caused by bacteria or yeasts (fungi). The antimicrobial and antifungal activity of the prepared compounds have been evaluated on a wide spectrum of bacterial and yeast strains and clinical specimens isolated from patients with infectious wounds and the best antimicrobial properties were observed in strains after the use of ligand abb and complex 1, when at least 80% growth inhibition was achieved.
Keywords: triaziny; molekulární struktura; Microbial Sensitivity Tests; coordination compounds; mikrobiální testy citlivosti; single crystal X-ray diffraction; benzimidazoly; Inhibitory Concentration 50; molekulární modely; Molecular Structure; benzimidazole; trimercaptotriazine; inhibiční koncentrace 50; trithiocyanuric acid; Anti-Infective Agents; biological activity; Triazines; antiinfekční látky; Benzimidazoles; Models, Molecular